STUDIES ON THE SITE-SELECTIVE N-ACYLIMINIUM ION CYCLIZATION - SYNTHESIS OF (PLUS-OR-MINUS)-GLOCHIDINE AND (PLUS-OR-MINUS)-GLOCHIDICINE - LEE, YS; KIM, SH; JUNG, SH; LEE, SJ; PARK, H (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
Studies on the N-acyliminium ion cyclization of hydroxylactams bearing both carbon and nitrogen nucleophile in the same molecule are described. The site selection ill the cyclization of hydroxylactam could be controlled by the absence or presence of acid catalyst to afford (+/-)-glochidine and (+/-)-glochidicine.